Minimal peace in Northeast Asia: a realist-liberal explanation - Singh, Bhubhindar (2022)
Northeast Asia is usually associated with conflict and war. Challenging this prevailing view, this article shows that the sub-region has achieved minimal peace since its peaceful transition from the Cold War to the post-Cold War period. The questions posed are: (a) what factors are responsible for Northeast Asia’s minimal peace?; and (b) how will these factors respond to the worsening US-China competition since 2010? This article’s argument is two-fold. First, Northeast Asia’s minimal peace is explained by three realist-liberal factors: America’s hegemony; strong economic interdependence among the Northeast Asian states; and a stable institutional structure in East Asia, including Northeast Asia. These factors kept a stable balance of power, ensured development and prosperity, and mitigated the political and strategic tensions between the states. Second, Northeast Asia’s minimal peace would be durable to counter the negative effects of the Sino-US competition in the coming decades. While the economic interdependence and institutional building factors have shown resilience, the US hegemony faces a robust challenge from China. Nevertheless, the US hegemony is durable because of America’s enduring relative strategic and economic advantages over China, the expanded role of America’s regional allies to preserve US preponderance and China’s problems in building an alternative regional order.